Critical Analysis of Socio-Cultural Factors in the Problematics of Memorizing the Qur'an: A Case Study at the Al Qonitat Miftahun Najah Islamic Boarding School in Jepara - Rosyidah, Afifatur; Saefudin, Ahmad (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study explores the influence of socio-cultural factors on the memorisation of the Qur’an (tahfiz) in Islamic boarding schools, a dimension often overlooked despite its critical role in students’ learning success. Focusing on the Al Qonitat Miftahun Najah Islamic Boarding School in Jepara, the research aims to analyse how social environments, cultural traditions, and peer interactions impact the tahfiz process. Employing a qualitative case study approach, data were collected from 20 purposively selected students through interviews, observations, and documentation, and analysed thematically. The findings reveal that family support, institutional motivation, and entrenched religious traditions serve as key enablers, while social pressure, cultural differences, and the rigid routines of pesantren life present significant challenges. These results align with social learning theory, emphasizing the role of collective interaction in shaping educational behaviour. The study concludes that socio-cultural dynamics play a decisive role in the success of Qur’anic memorisation. Practically, the findings suggest that enhanced collaboration between families and educational institutions is essential to cultivating a more supportive and sustainable learning environment.